2014
DOI: 10.1371/journal.pone.0107268
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nicotine Dependence on the Relationship between Variants in the Nicotinic Receptor Genes and Risk of Lung Adenocarcinoma

Abstract: Several variations in the nicotinic receptor genes have been identified to be associated with both lung cancer risk and smoking in the genome-wide association (GWA) studies. However, the relationships among these three factors (genetic variants, nicotine dependence, and lung cancer) remain unclear. In an attempt to elucidate these relationships, we applied mediation analysis to quantify the impact of nicotine dependence on the association between the nicotinic receptor genetic variants and lung adenocarcinoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 78 publications
(80 reference statements)
2
20
1
Order By: Relevance
“…Various meta-analyses based on subjects of European ancestry identified robust associations for rs16969968 in the gene CHRNA5 and rs1051730 in the CHRNA3 with smoking quantity (number of cigarettes smoked per day) [7, 14, 15, 17]. Especially, rs16969968, a nonsynonymous variant, was indicated with functions of altering nicotinic receptor conductance in vitro by amino acid change in the CHRNA5 [7, 18, 19]. Those two loci have been found to be associated with lung cancer, chronic obstructive pulmonary disease and body mass index in never smokers [13, 2023].…”
Section: Discussionmentioning
confidence: 99%
“…Various meta-analyses based on subjects of European ancestry identified robust associations for rs16969968 in the gene CHRNA5 and rs1051730 in the CHRNA3 with smoking quantity (number of cigarettes smoked per day) [7, 14, 15, 17]. Especially, rs16969968, a nonsynonymous variant, was indicated with functions of altering nicotinic receptor conductance in vitro by amino acid change in the CHRNA5 [7, 18, 19]. Those two loci have been found to be associated with lung cancer, chronic obstructive pulmonary disease and body mass index in never smokers [13, 2023].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, validated questionnaires for nicotine dependence or biomarkers for nicotine consumption such as cotinine are not available within the SIBDCS data set. As such, though there is an extensive body of literature supporting the association of these smoking quantity‐associated SNPs with variables other than number of cigarettes per day: patient cotinine and carbon monoxide levels and nicotine dependence . However, without these data we cannot distinguish, whether the interaction of genetic risk with smoking in IBD patients is mediated via the number of cigarettes per day or in addition via a different smoking topography (ie deeper inhalation, number of puffs per cigarette).…”
Section: Discussionmentioning
confidence: 97%
“…In a study of variants of the nicotinic receptor genes and the association with both smoking dependence and adenocarcinoma of the lung, two CHRNA3 SNPs were most associated with nicotine dependence and adenocarcinoma of the lung [35]. They demonstrated that variations in these genes significantly affect the risk for adenocarcinoma of the lung.…”
Section: Methodsmentioning
confidence: 99%